Review on superbug - Hitendra Jadon; Ashish Chauhan (Current Research in Pharmaceutical Sciences, 2011)
Staphylococcus aureus is a common cause of infection in both hospitals and the community, and it is becoming increasingly virulent and resistant to antibiotics. The recent sequencing of seven strains of S. aureus provides unprecedented information about its genome diversity. Subtle differences in core (stable) regions of the genome have been exploited by multi-locus sequence typing (MLST) to understand S. aureus population structure. Dramatic differences in the carriage and spread of accessory genes, including those involved in virulence and resistance, contribute to the emergence of new strains with healthcare implications. Understanding the differences between S. aureus genomes and the controls that govern these changes is helping to improve our knowledge of S. aureus pathogenicity and to predict the evolution of super-superbugs.